2008
DOI: 10.1111/j.1365-2575.2008.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Business–IT fit in e‐procurement systems: evidence from high‐technology firms in China

Abstract: Because of the influence of globalization and updated information technologies (IT), firms in China face an urgent need to adopt e-procurement systems (EP) to deal with their daily procurement activities. However, implementing EP in China encounters various uncertainties from internal and external business environments. To address this issue, this research aims to examine the fit between business and the IT environment and to study its impact on system performance. The literature review allows the proposal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Furthermore, studies adopting an alternative approach in measuring procurement alignment, validate their hypothesis through theoretical reasoning [32], or through a small number of case studies in a specific region [15]. Hence, the positive association of procurement alignment on supply chain management performance cannot be confirmed with certainty.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Furthermore, studies adopting an alternative approach in measuring procurement alignment, validate their hypothesis through theoretical reasoning [32], or through a small number of case studies in a specific region [15]. Hence, the positive association of procurement alignment on supply chain management performance cannot be confirmed with certainty.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…It has been shown in a single longitudinal case study that the lack of IT alignment prevents the development of IT competency in the company (Chen, Sun, Helms, & Jih, 2008). Further, a case study in four Chinese companies has shown that the lack of alignment between the business environment and IT caused additional IT implementation costs (Chang, Wang, & Chiu, 2008).…”
Section: Business Role Of It/ismentioning
confidence: 98%
“…The impact of electronic commerce on procurement processes in the supply chain was presented, which highlighted the risks and uncertainties of buyers, sellers, and the transaction processes involved [50]. Chang et al [6] evaluated the impact of uncertainties in the environment, partnership and process on e-procurement performance. Other studies have analyzed and investigated the failure of several electronic markets.…”
Section: E-procurementmentioning
confidence: 99%